INTEGRASI PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN (Studi di SDN Indrasari 1 Martapura) - Adawiah, Rabiatul (Vidya Karya Jurnal Kependidikan, 2015)
The condition of the nation which is increasingly distant from the values of the character and culture of the nation, made the Government through Kemendikbud since 2010 launched the character education as a national movement throughout the educational level. One of the way was integration character education into learning activities. This research aimed to develop character values through learning by applying qualitative approach. The data collected by observation and interview, then analyzed by interactive models of analysis. The results showed that in the effort to develop character values, SDN Indrasari 1 Martapura has been organizing the class as well. In carrying out the process of learning, teachers use scientific approach, by involving students into the learning process through some activities such as observing, questioning, trying, reasoning, and communicating. Assessment which is conducted by teacher refers to the four core competencies, namely spiritual, social attitudes, knowledge, and skills. In carrying out the process of learning, some teachers have been successfully developed the character values such as religious character , responsibility, discipline, cooperation, accuracy, honesty and decency.